2010
DOI: 10.5194/acp-10-2037-2010
|View full text |Cite
|
Sign up to set email alerts
|

Numerical simulations of contrail-to-cirrus transition – Part 2: Impact of initial ice crystal number, radiation, stratification, secondary nucleation and layer depth

Abstract: Abstract.Simulations of contrail-to-cirrus transition were performed with an LES model. In Part 1 the impact of relative humidity, temperature and vertical wind shear was explored in a detailed parametric study. Here, we study atmospheric parameters like stratification and depth of the supersaturated layer and processes which may affect the contrail evolution. We consider contrails in various radiation scenarios herein defined by the season, time of day and the presence of lower-level cloudiness which controls… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
66
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 60 publications
(68 citation statements)
references
References 28 publications
2
66
0
Order By: Relevance
“…Unterstrasser and Gierens (2010) (Fig. 1) showed that these two competing effects nearly cancel each other.…”
Section: Referencementioning
confidence: 90%
“…Unterstrasser and Gierens (2010) (Fig. 1) showed that these two competing effects nearly cancel each other.…”
Section: Referencementioning
confidence: 90%
“…The turbulent velocity accounts for the sub-grid scale turbulent dispersion via the TKE equation. The EULAG model has been extensively used for aviationrelated numerical modelling in the past (Unterstrasser et al, 2008;Unterstrasser and Gierens, 2010b;Jeßberger et al, 2013).…”
Section: Eulag-lcmmentioning
confidence: 99%
“…Microphysical properties of contrails depend a lot more on the number of ice crystals than on the ice mass after the vortex phase (Unterstrasser and Gierens, 2010b). Therefore, it is appropriate to explicitly prescribe an initial ice crystal number concentration instead of an initial ice mass.…”
Section: Initial Values For Contrailsmentioning
confidence: 99%